The Influence of Training and Career Development to Employee Performance Among Academic Civities At Sekolah Tinggi Ilmu Ekonomi Muara - Sofia, Sofia (International Journal for Educational and Vocational Studies, 2020)
One important factor in sustaining the company's existence in advancing quality and performance management is the mastery of capabilities possessed by human resources and the clarity of career development. A clean and healthy company is certainly due to good employee performance. Employee performance will improve if employees are given the training to improve their abilities and also a clear career development program. This study aims to determine the effect of training and career development on employee performance. The unit of analysis in this study is individual employees of academic civities. The population in this study is all employees of academic civities which amounted to 63 employees. The sampling technique in this study was carried out with saturated sampling technique. The data analysis technique used is multiple linear analysis. The results showed that training and career development both partially and simultaneously had a significant effect on employee performance.